Dyscalculia from a developmental and differential perspective. - Kaufmann, L; Mazzocco, M; Dowker, A; von Aster, M; Göbel, S; Grabner, R; Henik, A; Jordan, N; Karmiloff-Smith, A; Kucian, K; Rubinsten, O; Szucs, D; et al. (Frontiers Media S.A., 2013)
Developmental dyscalculia (DD) and its treatment are receiving increasing research attention. A PsychInfo search for peer-reviewed articles with dyscalculia as a title word reveals 31 papers published from 1991-2001, versus 74 papers published from 2002-2012. Still, these small counts reflect the paucity of research on DD compared to dyslexia, despite the prevalence of mathematical difficulties. In the UK, 22% of adults have mathematical difficulties sufficient to impose severe practical and occupational restrictions (Bynner and Parsons, 1997; National Center for Education Statistics, 2011). It is unlikely that all of these individuals with mathematical difficulties have DD, but criteria for defining and diagnosing dyscalculia remain ambiguous (Mazzocco and Myers, 2003). What is treated as DD in one study may be conceptualized as another form of mathematical impairment in another study. Furthermore, DD is frequently-but, we believe, mistakenly- considered a largely homogeneous disorder. Here we advocate a differential and developmental perspective on DD focused on identifying behavioral, cognitive, and neural sources of individual differences that contribute to our understanding of what DD is and what it is not. © 2013 Kaufmann, Mazzocco, Dowker, von Aster, Göbel, Grabner, Henik, Jordan, Karmiloff-Smith, Kucian, Rubinsten, Szucs, Shalev and Nuerk.